IL-33-mediated mast cell and eosinophil function requires isoprenylation - Burchett, Jason R.; Kotha, Aditya; Davis, Destiny T.; Jackson, Kaitlyn G.; Dailey, Jordan M.; Maldonado, Tania D.; Haque, Tamara T.; Hussain, Zakaria Y.; Ching, John M.; Frischmeyer-Guerrerio, Pamela; Sebti, Said M.; Ryan, John J. (Frontiers in Immunology, 2025)
IntroductionAllergic disease is a common and symptomatically heterogeneous group of inflammatory disorders marked by overactive Th2 and mast cell (MC) responses along with eosinophil infiltration. Treatment options require continual assessment due to breakthrough symptoms on standard regimens. One approach to improved therapy is drug repurposing. Our lab previously showed that cholesterol-lowering statin drugs can suppress IgE-mediated mast cell function by inhibiting protein isoprenylation, a pathway using cholesterol biosynthesis intermediates. Additionally, mast cells are activated by the alarmin IL-33, released by epithelial cells after contact with cellular stressors. We hypothesized that IL-33-mediated mast cell function can be inhibited by disrupting isoprenylation via statins or the dual farnesyltransferase (FT) geranylgeranyltransferase-1 inhibitor, FGTI-2734.MethodsWe used IL-33 to stimulate mast cells and eosinophils in vitro and inhibited their function using simvastatin and FGTI-2734. Using primary mast cells and eosinophils, we measured cytokine production by ELISA and qPCR. Flow cytometry and western blots were used to measure phosphorylation of IL-33 signaling components, and eosinophil migration. Human mast cells were assessed by ELISA for cytokine inhibition. Lastly, a murine model of IL-33 induced peritonitis was used to assess the effects of isoprenylation inhibition on eosinophil and neutrophil influx.ResultsWe show simvastatin and FGTI-2734 suppressed IL-33-mediated cytokine protein and mRNA production in primary murine mast cells from the C57BL/6 strain. Simvastatin effects were lost on mast cells from the 129/SvJ strain and were inconsistent among primary human mast cells. In contrast, FGTI-2734 inhibited IL-33-induced cytokine production by mast cells on the 129/SvJ strain and among human donors. Simvastatin and FGTI-2734 also inhibited IL-33-induced cytokine production and chemokine-induced migration of C57BL/6 primary eosinophils. Simvastatin and FGTI-2734 had no effect on expression of the IL-33 receptor, ST2, suggesting that inhibition occurs at a step in IL-33 signaling. Importantly, FGTI-2734 significantly reduced eosinophil and neutrophil influx in a model of IL-33-induced peritonitis, whereas simvastatin had no effect.DiscussionThese findings indicate that targeting FT and GGT-1 is a viable target in IL-33-induced inflammation.